Transactions of the American Society of Civil Engineers. (New York, American Society of Civil Engineers., 1867)
Vols. 29-30 include papers of the International Engineering Congress, Chicago, 1893; v. 54 includes papers of the International Engineering Congress, St. Louis, 1904.
Keywords: Civil engineering -- Periodicals; Engineering; Civil engineering; Civil engineering -- Periodicals